Cervical Vestibular Evoked Myogenic Potentials in Benign Paroxysmal Positional Vertigo: A Systematic Review and Meta-Analysis - Chen, Gang; Yu, Gang; Li, Yun; Zhao, Xuening; Dai, Xiaoyan; Wang, Guotao (Frontiers in Neurology, 2019)
Objective: The objective of our study was to investigate the potential association between the occurrence of benign paroxysmal positional vertigo (BPPV) and saccular dysfunction using cervical vestibular evoked myogenic potentials (cVEMP) testing. Methods: The databases including Pubmed, Embase and CENTRAL were systemically searched for case-control literatures investigating saccular dysfunction using cVEMP testing in BPPV patients compared with healthy controls. The literatures were published up to 16 April 2019 and were limited to the English language. All statistical processes were carried out using software Review Manager, version 5.3. Subgroup analysis and sensitive analysis were performed simultaneously. Results: Of the 12 case-control studies confirmed for meta-analysis, p13 latency of cVEMP was assessed in 8 studies, n23 latency in 6 studies, amplitude in 5 studies, asymmetry ratio (AR) in 3 studies, proportion of absent response in 9 studies, abnormal cVEMP in 8 studies. Compared with healthy controls, the p13 mean latency of cVEMP was longer (MD=0.88, 95%CI=0.64-1.12, p<0.00001), the mean amplitude was lower (SMD=-0.60, 95%CI=-0.80 to -0.41, p<0.00001), and the proportions of absent response (OR=8.76, 95%CI=2.28-33.61, p=0.002) and abnormal cVEMP (OR=7.47, 95%CI=4.65-12.01, p<0.00001) were higher in BPPV patients. But there was no significant difference in the n23 mean latency (MD=0.37, 95%CI=-0.23-0.98, p=0.22) and the AR of cVEMP (MD=3.95, 95%CI=-4.75-12.65, p=0.37) between BPPV patients and healthy controls. In the sub-group analysis based on age, only the result of the proportion of absent response of cVEMP indicated a significant difference existed (p=0.002) between the studies with age-matched controls (OR=2.78, 95% CI=1.09-7.10, p=0.03) and the studies without age-matched controls (OR=53.85, 95% CI=10.09-287.13, p<0.00001). In the sub-group analysis of the proportion of abnormal cVEMP according to the diagnostic criteria of abnormal cVEMP, the result indicated no significant difference existed between the four groups (p=0.61, I2=0%). In the sensitivity analysis, we obtained the consistent results after removing each study sequentially. Conclusion: The meta-analysis reveals that saccular dysfunction may be associated with BPPV occurrence, and neural degeneration in the saccular macula may be a potential pathogenesis for BPPV.